2014
DOI: 10.3748/wjg.v20.i36.13127
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum platelet derived growth factor BB levels in acute and increased in chronic pancreatitis

Abstract: The serum levels of some growth factors and cytokines differ significantly in AP, WOPN and CP. These data suggest that selected growth factors and cytokines may be considered as potential diagnostic biomarkers in patients with pancreatic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Among others, fibroblast growth factor and platelet-derived growth factor (PDGF) are the major cytokines that initiate and afterward support fibroblast proliferation and chemotactic activity resulting in the necrotic area encapsulation[ 26 - 28 ]. Clinical observations of Stojek et al [ 29 ] indirectly confirmed this assumption. According to findings of this scientific group, serum levels of PDGF-BB is significantly increased in patients with chronic pancreatitis, which is associated with chronic inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 74%
“…Among others, fibroblast growth factor and platelet-derived growth factor (PDGF) are the major cytokines that initiate and afterward support fibroblast proliferation and chemotactic activity resulting in the necrotic area encapsulation[ 26 - 28 ]. Clinical observations of Stojek et al [ 29 ] indirectly confirmed this assumption. According to findings of this scientific group, serum levels of PDGF-BB is significantly increased in patients with chronic pancreatitis, which is associated with chronic inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 74%
“…However, congruent findings by independent sources serve to increase overall confidence in the direction of expression change for these factors. Additionally, our study was focused on expression of factors in chronic pancreatitis rather than acute pancreatitis, a condition that may have a distinct profile of inflammatory mediators 17 .…”
Section: Discussionmentioning
confidence: 99%
“…PDGF-BB plasma levels in patients with aseptic loosening of their hip prosthesis were 40 (8.4) pg/mL (0.04 ng/mL), mean (SE), whereas those with stable prostheses, without clinical and radiological signs of loosening was 90 (16) pg/mL, determined by enzyme immunoassay (Cenni et al, 2005). Stojek et al (2014) found that healthy subjects were recorded to have serum PDGF-BB levels of 6.2 ± 0.76 ng/mL (mean ± SE) measured using ELISA. Another study reported a median serum concentration of PDGF-BB at 3.89 ng/mL in healthy participants measured using ELISA (Solchaga et al, 2013).…”
Section: Endogenous Level Of Pdgf-bb In Humanmentioning
confidence: 99%